The Practice of Introducing Restrictions on the Right to Freedom of Peaceful Assembly within Administrative Proceedings and the Place of the Judicial Branch of Power in Determining the Admissibility of Such Restrictions (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The author has researched the practice of the executive branch of power of Ukraine in establishing a collective (general) ban and restriction of the right to freedom of peaceful assembly under quarantine, as well as the place and role of the judicial branch of power represented by the Supreme Court and the Constitutional Court of Ukraine in determining the constitutionality of such restrictions and prohibitions.The powers of the Supreme Court on the constitutional submission to the Constitutional Court of Ukraine on the constitutionality of the Resolution of the Cabinet of Ministers of Ukraine “On quarantine to prevent the spread of acute respiratory disease COVID-19 caused by coronavirus SARS-CoV-2 and stages of weakening of anti-epidemic measures” dated from May 20, 2020 No. 392 on the establishment of a ban on the exercise of the right to freedom of peaceful assembly within administrative proceedings during the introduction of quarantine in Ukraine, as well as the justification of such a constitutional submission.It is important to analyze and form a legal understanding of the Decision of the Constitutional Court of Ukraine on the unconstitutionality of restricting and prohibiting the exercise of the right to freedom of peaceful assembly during quarantine within administrative proceedings – by adopting the relevant resolution by the Cabinet of Ministers of Ukraine, which was the result of administrative discretion of the highest agency in the system of executive agencies of Ukraine. In this regard, the study focuses on the motivation and validity of the decision of the agency of constitutional jurisdiction and understanding of those legal and social values that were the basis for the judges of the Constitutional Court of Ukraine while adopting the decision dated from August 28, 2020 No 10-r/2020.
Keywords: the right to freedom of peaceful assembly; quarantine; restrictions; the Supreme Court of Ukraine; the Constitutional Court of Ukraine; the constitutionality of restrictions.